2020
DOI: 10.1038/s41598-020-77685-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and classification of Romanian acacia honey based on its physicochemical parameters and chemometrics

Abstract: Three groups of Romanian acacia honey, i.e., pure, directly adulterated (by mixing the pure honey with three sugar syrups), and indirectly adulterated (by feeding the bees with the same syrups), were characterized and discriminated based on their physicochemical parameters. Moisture, ash, 5-hydroxymethylfurfural (HMF), reducing sugars (fructose and glucose), and sucrose contents, free acidity, diastase activity, ratio between stable carbon isotopes of honey and its proteins (δ13CH and δ13CP) were evaluated. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 34 publications
1
23
1
Order By: Relevance
“…On the other hand, our findings indicated slightly higher values compared to the data reported by other researchers (54.3-63.6% and 54.59-77.40%) [ 13 , 27 ]. Furthermore, a lower mean value (63.3%) has been reported in indirectly adulterated (syrups feeding) samples [ 7 ]. In another study performed in Iran (Ardabil Province), the level of reducing sugars in 6.11% the samples was considered unacceptable compared to the standard level [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, our findings indicated slightly higher values compared to the data reported by other researchers (54.3-63.6% and 54.59-77.40%) [ 13 , 27 ]. Furthermore, a lower mean value (63.3%) has been reported in indirectly adulterated (syrups feeding) samples [ 7 ]. In another study performed in Iran (Ardabil Province), the level of reducing sugars in 6.11% the samples was considered unacceptable compared to the standard level [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, higher sucrose contents were obtained in a study performed to monitor the quality of South African honey [ 30 ], in which sucrose values were reported to be 0-32.40%. In another study [ 7 ], the researchers concluded that mean sucrose was 9.71% in indirectly adulterated samples (syrup feeding of bees), which was higher than directly adulterated samples (adding sugar syrups to pure honey; 6.38%) and the pure samples (3.79%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glucose and fructose are the main sugars in honey and represent more than 70% of the composition of honey [5,6]. The water content of honey ranges from 10% to 20% [7].…”
Section: Introductionmentioning
confidence: 99%